Heralding a new era of oxytocinergic research: new tools, new problems? - Althammer, Ferdinand (Journal of neuroendocrinology, 2023)
According to classic neuroendocrinology, hypothalamic oxytocin cells can be categorized into parvo- and magnocellular neurons. However, research in the last decade provided ample evidence that this black-and-white model of oxytocin neurons is most likely oversimplified. Novel genetic, functional and morphological studies indicate that oxytocin neurons might be organized in functional modules and suggest the existence of five or more distinct oxytocinergic subpopulations. However, many of these novel, automated high-throughput techniques might be inherently biased and interpretation of acquired data needs to be approached with caution to enable drawing sound and reliable conclusions. In addition, the recent finding that astrocytes in various brain regions express functional oxytocin receptors represents a paradigm shift and challenges the view that oxytocin primarily acts as a direct peptidergic neurotransmitter. This review highlights the latest technical advances in oxytocinergic research, puts recent studies on the oxytocin system into context and formulates various provocative ideas based on novel findings that challenges various prevailing hypotheses and dogmas about oxytocinergic modulation.